(untitled) (Research Nepal Journal of Development Studies, 2025)
Urban development has become a critical focus in Nepal’s national development agenda due to rapid urbanization and the increasing need for sustainable infrastructure, housing, and public services. This study examines the trends, patterns, and proportion of government expenditure allocated to urban development in comparison to the overall development budget of Nepal. Using secondary data from government budget documents, economic surveys, and planning reports, the study analyzes how urban development spending has evolved over time and evaluates its alignment with national development priorities. The findings reveal that although urban development is gaining importance, it still constitutes a relatively small share of the total development budget. The research highlights challenges such as budget underutilization, uneven regional allocation, and limited integration of urban planning into national strategies. The study concludes that enhancing transparency, increasing targeted investment, and adopting a more holistic urban policy framework are essential for maximizing the impact of urban development expenditure in Nepal. Not only that, proper approval of policies from the concerned ministry should be approved in time to overcome unexpected urban population growth. Similarly, the budget on urban development with respect to the national development budget should be highly prioritized to make the city prosper and smart.